2006
DOI: 10.1007/s10683-006-5385-z
|View full text |Cite
|
Sign up to set email alerts
|

Neutral versus loaded instructions in a bribery experiment

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
129
7
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(151 citation statements)
references
References 55 publications
9
129
7
6
Order By: Relevance
“…4 He hypothesizes that offering the citizen legal impunity for whistle-blowing even if she has paid a bribe can encourage more frequent reporting. In turn, this should discourage officials from demanding bribes in 3 "Rs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 He hypothesizes that offering the citizen legal impunity for whistle-blowing even if she has paid a bribe can encourage more frequent reporting. In turn, this should discourage officials from demanding bribes in 3 "Rs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, about 44% of parents in several African countries were asked to pay bribes for admission to public schools for their children, (Transparency International, 2010). 4 A citizen feedback model being trailed in Pakistan (Callen and Hasanain, 2011) and Ghana's whistleblower act (Amegashie, 2013) have some similar features, with protection being granted to citizen whistleblowers and measures taken to empower them by registering their complaints.…”
Section: Introductionmentioning
confidence: 99%
“…In bribing games, Abbink & Hennig-Schmidt (2006) showed that there is no difference between individual behavior exposed to neutral and framed/contextualized instructions, while Barr & Serra (2009) reported the opposite finding. In public goods games, Cookson (2000) found that changing the presentational variables (e.g.…”
Section: Framing Effectsmentioning
confidence: 91%
“…However, in certain contexts it is impossible to avoid framing without making the task irrelevant. A number of studies examine the effect of framing in the instructions on individual behavior in the context of corruption (Abbink & Hennig-Schmidt, 2006;Barr & Serra, 2009), public goods games (Andreoni, 1995;Cookson, 2000;Park, 2000;Fujimoto & Park, 2010;, sequential bargaining games (Brosig et al, 2003), and altruistic giving in dictator games (Duffy & Kornienko 2010). The existing experiments manipulating the framing of instructions can be separated roughly into two categories: procedural-oriented framing (which compares the different ways of representing the problem, e.g.…”
Section: Framing Effectsmentioning
confidence: 99%
“…Experiments that investigate corrupt decisions randomly allocate subjects to the role of the briber and of the public official, and allow subjects to decide whether to offer a bribe and to accept it, respectively (Abbink et al 2000(Abbink et al , 2002(Abbink et al , 2014Abbink 2004;Abbink and Hennig-Schmidt 2006;Abbink and Wu 2017). We do not allocate subjects randomly to the different roles for ethical and experimental reasons.…”
Section: Methodsmentioning
confidence: 99%